Complexes of π-prismands with gallium(I) - Kunze, Andreas; Gleiter, Rolf; Bethke, Sabine; Rominger, Frank (Organometallics, 2006)
A stable complex between the π-prismand 4,10,15-(1,4)tribenzena-1,7-diazabicyclo[5.5.5]heptadecaphane (2) and Ga(I) was synthesized. X-ray investigations on single crystals of [Ga·2]+[GaCl4]- revealed that the Ga atom is situated in the center of the cage and is totally separated from the anion. The reaction of 2 with Tl(CH3CO2) yielded [Tl·2]+[CH3CO2]-. Spectroscopic evidence is provided for the existence of [Tl·2]+ by a strong coupling between the 13C nuclei of the arene part of the ligand and the metal. DFT calculations on [Ga·2]+, [In·2]+, and [Tl·2]+ suggest bonding between the metal and the arene rings as well as the nitrogen atoms.